Latest developments, assessments and research trends for next generation of concentrated solar power plants using liquid heat transfer fluids. (October 2022) - Arias, I.; Cardemil, J.; Zarza, E.; Valenzuela, L.; Escobar, R.
Abstract: Solar thermal technologies for power generation have become cost-effective, efficient, flexible, and play a prominent role in achieving low-carbon energy systems. Concentrated solar power is the main solar technology for large-scale power generation and can offer thermal energy storage capacity, delivering power to the grid with high reliability, high capacity factor and low cost. However, their operation is constrained by the maximum temperature allowable for the heat transfer fluids used (up to 565 °C using molten salts). Continuous efforts are in progress to demonstrate the scalability, reliability, functionality, and performance of different concentrated solar thermal components and liquid heat transfer fluids for third-generation concentrated solar power plants. Third-generation concentrated solar power plants are characterized by: (a) operating at temperatures above 700 °C and (b) increasing the capacity, reliability, efficiency and stability of the system network. To date, several authors have evaluated the performance of novel liquid, solid particles and gaseous/supercritical heat transfer fluids, triggering intense development of new receivers, enhanced heat exchangers, storage systems, new materials, and their aging tests, among others. The present study compiles the recent literature referred to the liquid-pathway of third-generation concentrated solar power plants, emphasizing the relevant lines of research and the issues to be resolved in the coming years on high-temperature receivers, heat transfer fluids and storage concepts, as well as suitable high-temperature thermodynamic cycles. Highlights: A liquid-pathway overview of Gen3 CSP plants is presented. Latest scientific advances concerning liquid-based Gen3 CSP plants are included. LCOE reductions of up to 10% are reported in the literature. Research gaps and future prospects are identified.